First record of Anthopotamus verticis and new records of A. Distinctus (Ephemeroptera: Potamanthidae) in New England - Burian, S.K. (Entomological News, 1997)
The species Anthopotamus verticis is recorded for the first time in New England from the Housatonic River in western Connecticut. Notes on the larval habitat and observations on the sympatric occurrence of this species with A. distinctus are presented. New distribution records for A. distinctus are presented for Massachusetts and Vermont.
Keywords: Anthopotamus distinctus; Anthopotamus verticis; dept.bio; ⛔ No DOI found